2012
DOI: 10.1371/journal.pone.0038279
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Novel Peptide Ligand Targeting Human Carbonic Anhydrase IX

Abstract: BackgroundCarbonic anhydrase IX (CA IX) is a hypoxia-regulated transmembrane protein over-expressed in various types of human cancer. Recently, a new peptide with affinity for human carbonic anhydrase IX (CaIX-P1) was identified using the phage display technology. Aim of the present study is to characterize the binding site in the sequence of CaIX-P1, in order to optimize the binding and metabolic properties and use it for targeting purposes.Methodology/Principal FindingsVarious fragments of CaIX-P1 were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
12
1
2
Order By: Relevance
“…Flow cytometry experiments indicated ligand‐dependent binding of Alexa546 and IRDye750 conjugates 1 b and 1 c – 5 c to CAIX‐positive cells (Figure 1 b, Figure 1 in the Supporting Information (SI)), but not to control cell lines lacking CAIX (Figures 2 and 3 (SI)). In contrast to previous reports that suggested receptor‐based internalization of CAIX‐specific ligands,2225 acetazolamide‐based fluorophore conjugates were found to preferentially bind to the cell membrane of kidney cancer cells without efficient internalization (Figure 1 c, Figure 5 (SI)), while the same cells were not stained by fluorophores lacking the tumor‐homing moiety (Figure 1 d). These results collectively suggest that fluorescent probes 1 a – c derived from the approved antiglaucoma drug acetazolamide (AAZ) were high‐affinity CAIX binders ( K D =12.6 n M for 1 a ) and, thus, potentially suitable for pharmacodelivery applications.…”
Section: Methodscontrasting
confidence: 99%
“…Flow cytometry experiments indicated ligand‐dependent binding of Alexa546 and IRDye750 conjugates 1 b and 1 c – 5 c to CAIX‐positive cells (Figure 1 b, Figure 1 in the Supporting Information (SI)), but not to control cell lines lacking CAIX (Figures 2 and 3 (SI)). In contrast to previous reports that suggested receptor‐based internalization of CAIX‐specific ligands,2225 acetazolamide‐based fluorophore conjugates were found to preferentially bind to the cell membrane of kidney cancer cells without efficient internalization (Figure 1 c, Figure 5 (SI)), while the same cells were not stained by fluorophores lacking the tumor‐homing moiety (Figure 1 d). These results collectively suggest that fluorescent probes 1 a – c derived from the approved antiglaucoma drug acetazolamide (AAZ) were high‐affinity CAIX binders ( K D =12.6 n M for 1 a ) and, thus, potentially suitable for pharmacodelivery applications.…”
Section: Methodscontrasting
confidence: 99%
“…Rana et al . attempted to optimize the stability and binding properties of CaIX-P1 by performing alanine scanning and truncation studies 71 . This led to the identification of NHVPLSPy (CaIX-P1-4-10) as a candidate.…”
Section: Peptidesmentioning
confidence: 99%
“…Recently, a new peptide (CaIX-P1) with specificity for the extracellular domain of CAIX was identified by phage display technology using a commercially available Ph.D.12 library and the CAIX binding affinity and biodistribution studied (207). Although the stability and affinity of CaIX-P1 was recently optimized, organ distribution studies revealed low tumor-to-blood ratios and high background distribution, which is not favorable for imaging applications (208). Therefore, further research is required for generation of peptide-based ligands with high target specificity for human carbonic anhydrase IX.…”
Section: Caix and Caxii Selectivity Issuesmentioning
confidence: 99%